2018
DOI: 10.1115/1.4040349
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heterogeneous Joule Heating as the Explanation for the Transient Electroplastic Stress Drop in Pulsed Tension of 7075-T6 Aluminum

Abstract: The electroplastic effect can be predicted and modeled as a 100% bulk heating/softening phenomenon in the quasi-steady-state; however, these same models do not accurately predict flow stress in transient cases. In this work, heterogeneous Joule heating is examined as the possible cause for the transient stress drop during quasi-static pulsed tension of 7075-T6 aluminum. A multiscale finite element model is constructed where heterogeneous thermal softening is explored through the representation of grains, grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In correspondence of regions with different electrical resistivity (grain and phase boundary, dislocation tangles, dislocation sub cell walls etc.) there could be stagnation of electrons as proposed by Ruszkiewicz et al [15]. Electron stagnation could cause local increase in electron to atom ratio, leading to lowering the bonding energy between the ions of the crystal structure therefore easing dislocation motion in the case of current applied during deformation [58].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In correspondence of regions with different electrical resistivity (grain and phase boundary, dislocation tangles, dislocation sub cell walls etc.) there could be stagnation of electrons as proposed by Ruszkiewicz et al [15]. Electron stagnation could cause local increase in electron to atom ratio, leading to lowering the bonding energy between the ions of the crystal structure therefore easing dislocation motion in the case of current applied during deformation [58].…”
Section: Discussionmentioning
confidence: 96%
“…The discovery of such phenomenon led to the development of new approaches to material forming known as electrically assisted manufacturing (EAM) in which electrical current increases the formability of various metallic alloy exploiting the electroplastic effect (EPE). The electroplastic effect has shown to improve the formability on a wide variety of metallic materials such as aluminum [15][16][17], titanium [18][19][20], magnesium [21][22][23], stainless steels [24,25] and on a variety of forming processes as well. Some of the authors observed a relationship of the onset of EPE on FCC materials with respect the stacking fault energy (SFE), which drives dislocation's motion within the material [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of such phenomenon led to the development of new approaches to material forming known as electrically assisted manufacturing (EAM) in which electrical current increases the formability of various metallic alloy exploiting the Electroplastic effect (EPE). Electroplastic effect has shown to improve the formability on a wide variety of metallic materials such as aluminum [15][16][17], titanium [18][19][20], magnesium [21][22][23], stainless steels [24,25] and on a variety of forming process as well. Some of the authors observed a relation of the onset of EPE on FCC materials depending on the SFE, which drives dislocation's motion within the material [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the mechanisms induced by the electrical current are: electron wind force (transfer of momentum of conducting electron to dislocations increasing their mobility) [33], magnetoplastic effect (depinning of dislocations from weak obstacle thanks to the induced magnetic field) [34], electron stagnation theory (localized change in resistivity causes an increase of the electron to atom ratio, weakening the metallic bond and easing its breaking and restoration) [15], electromigration (increase of ions diffusivity because of the electrical current ) [35], reduced Gibbs free energy during phase transformation [36,37] and localized microscale joule heating [38].…”
Section: Introductionmentioning
confidence: 99%